Subsydia kapitałowo-inwestycyjne jako forma pomocy publicznej - Podsiadło, Piotr (Equity Participations as a Means of State Aid, 2009)
The goal of the article is to analyze the existing structure as well as the future directions of the state aid in the form of equity participations in Poland as compared to other member states of the European Union. The capital-investment subsidies cover both the help granted in the form of paid-in share capital and the money given in return for the conversion of liability onto the interests or shares. The state aid granted in Poland as equity participations can be analyzed on the basis of two time periods. Until the Polish accession to the European Union a much bigger share of the public help was granted in the form of the conversion of liability onto the interests or shares. Since 2004 the equity participations have only been granted by the state as paid-in share capital for the applying enterprises in return for taking over of a given number of interests or shares (partial nationalization), which could later be sold back to the enterprise after it has been restructured and regained the possibility for settling its own commitments. The latter solution seems to be better in comparison to taking over the shares as a consequence of state debt remission in the sense that the fact of additional capital channeled into the company can and should lead to repair processes in the enterprise. Debt remission is, as it seems, an immediate relief of short-term and it only tends to solve the problem of current insolvency. In any case, though, the state aid does not bear any real chances for its beneficiaries and does not help them stay on the market for a longer period of time. In European Union member states the state aid of paid-in share capital and conversion of liability onto the interests or shares is granted infrequently and makes for a small part of the overall public help granted in many forms. For the years 2005-2007 the overall value of equity participations for all 27 member states was €326 million, while at the same time the value of grants only was €23 billion, and of exemptions and tax reliefs - over €19 billion. The intensity of the subsidies corresponds to 1% of the overall state aid structure. This tendency, however, is likely to change anytime soon as in the time of economic recession the well directed social assistance may become an essential supplement to actions which are aimed at unblocking of enterprise loans and supporting investments in new technologies
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 233-243